Study on protective effect of Salvia miltiorrhiza extract on mesangial proliferative glomerulonephritis in rats based on the NLRP3/caspase 1 pathway - QIU Peng; NI Xiao-na (Linchuang shenzangbing zazhi)
Objective To investigate the protective effect of Salvia miltiorrhiza extract on mesangial proliferative glomerulonephritis(MsPGN) rats based on the NLRP3/caspase 1 pathway. Methods A total of 48 rats were selected to establish MsPGN models and randomly divided into 4 groups:(1)model group, not administered with any drug;(2)Salvia miltiorrhiza extract group, administered gastrically with Salvia miltiorrhiza extract(10 mL/kg) every day;(3)VX-765 group, administered with VX-765(NLRP3 inflammatory body inhibitor, dosage: 50 mg/kg)every day, by intraperitoneal injection;(4)Salvia miltiorrhiza extract + VX-765 group, administered gastrically with Salvia miltiorrhiza extract(10 mL/kg) every day, and with VX-765( 50 mg/kg)by intraperitoneal injection. Another 12 rats were used as the sham operation group. The treatment time for each group was 28 days. At 24 hours after the last administration, 24-hour urine of rats in each group was collected to detect the 24 h-urinary protein content. The levels of BUN, Scr, IL-1β and IL-18 were detected in serum of rats in each group. Hematoxylin-eosin(HE) staining was used to detect the pathological changes of kidney tissues of rats in each group. Pathological scores were made according to the degree of proliferation of mesangial cells and tubulointerstitial lesions, and the expressions of NLRP3 and caspase-1 in kidney tissues of rats in each group were detected by real-time fluorescence quantitative PCR and immunoblotting. Results Compared with the sham operation group, in the model group, some renal pathological damage symptoms, including increased glomerular volume, increased number of internal cells, diffused mesangial cell proliferation, increased cell matrix, renal interstitial inflammatory cell infiltration, occurred; glomerular mesangial cell proliferation score, tubulointerstitial pathological score, urinary protein content, serum BUN, Scr, IL-1β and IL-18 levels, NLRP3 and caspase-1 expressions increased significantly(P<0.05). Compared with the model group, in the Salvia miltiorrhiza extract group, VX-765 group and Salvia miltiorrhiza extract +VX-765 group, the above pathological damage symptoms were alleviated; glomerular mesangial cell proliferation score, tubulointerstitial pathological score, the urinary protein content, serum BUN, Scr, IL-1β and IL-18 levels, NLRP3 and caspase-1 expressions were all decreased(P<0.05). Compared with the Salvia miltiorrhiza extract group and VX-765 group, in the Salvia miltiorrhiza extract + VX-765 group, the above pathological damage symptoms were further alleviated; and glomerular mesangial cell proliferation score, tubulointerstitial pathological score, the urinary protein content, serum BUN, Scr, IL-1β and IL-18 levels, NLRP3 and caspase-1 expressions were all decreased in Salvia miltiorrhiza extract + VX-765 group(P<0.05). Conclusions Salvia miltiorrhiza extract can alleviate the Inflammatory reaction and mesangial proliferative lesions of rats, protect rat kidney tissues and repair rat kidney function, possibly achieved by down-regulating the NLRP3/caspase 1 pathway.